Effectiveness of Health Education on Self-care and Self-efficacy of Patients with Coronary Heart Disease: A Systematic Review - Rita Rita; Azizah Khoiriyati; Erna Rochmawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Coronary heart disease is a leading cause of morbidity and mortality worldwide. Health education is needed to improve patient self-care and self-efficacy. This research aims to synthesize the literature on health education, focusing on self-care outcomes and self-efficacy among patients with coronary heart disease. A systematic review was conducted through a literature search on ScienceDirect, PubMed, Wiley Online Library, and Scopus. The search strategy used a combination of keywords with the Boolean operators "AND" and "OR." Study selection was performed by screening titles, abstracts, and full texts in Rayyan. The methodological quality of articles meeting the inclusion criteria was assessed using the Joanna Briggs Institute (JBI) instrument. Of the 3,520 identified articles, five studies with a total of 958 coronary heart disease patients met the inclusion criteria. The interventions evaluated included diversified and staged health education, eHealth cardiac rehabilitation, a workbook in health education, web-based education, and problem-based learning. Overall, Diversified and Staged Health Education, eHealth Cardiac Rehabilitation, and Workbook in Health Education were effective in improving self-care and self-efficacy. Furthermore, a problem-based educational approach had a positive impact on self-efficacy. Findings indicate that multifaceted and phased health education effectively improves self-care, and eHealth cardiac rehabilitation and workbooks in health education have been shown to increase self-efficacy in patients with coronary heart disease. These improvements in self-care and self-efficacy have the potential to support cardiovascular risk factor management and improve patient health outcomes. Health education based on diversified and staged health education, eHealth cardiac rehabilitation, and workbook in health education is effective in improving self-care and self-efficacy in coronary heart disease patients. Integrating these interventions into coronary heart disease service standards has the potential to improve the quality of care, prevent complications, and reduce the risk of rehospitalization. Keywords: Coronary Heart Disease, Health Education, Self-Care, Self-Efficacy.